NOVEL PERGI KARYA TERE LIYE: ANALISIS KONFLIK BATIN TOKOH UTAMA - Husna, Nadyatul; Andayani, Andayani; Ulya, Chafit (Paramasastra: Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
The purpose of this research are to describe the intrinsic elements and inner conflicts of the main characters in the novel Pergi. This research is a descriptive research using content analysis method and using literary psychology approach which is conducted for six months, starting from May 2018 to October 2018. The source of data used in this study is in the form of documents and interviews. Documents in the form ofÂ  Novel Pergi by Tere Liye. The research subject was taken by purposive sampling technique. Data collection is done by analyzing documents and interviews. Validity test used is triangulation of theory and source triangulation. Data analysis techniques used are interactive model analysis which includes data collection, reduction activities, data presentation, and conclusion drawing. The research procedure consists of the preparation stage, the implementation phase, and the report preparation phase. The results of this study indicate the following two things. First, Novel Pergi has complete intrinsic elements consisting of 7 elements. Second, the Bujang character has an element of id, ego, and superego, which sometimes between the three is not in line and causes inner conflict within him.